PENGARUH PENGELOLAAN SEKTOR PUBLIK TERHADAP KINERJA DENGAN BERBAGAI FAKTOR MODERASI DI SATUAN KERJA PEMERINTAH DAERAH - Handoko, Trio (Surakarta Management Journal, 2020)
The measurement of public sector performance improvement (PSP) cannot be determined by just oneindicator, but it requires measurement of various collaborating indicators. After determining thecollaborative indicators, the implementation of PG is expected to increase. This research will usevarious PG indicators such as openness and accountability, political stability and absence of violence,government effectiveness, regulatory quality, rule of law, and corruption control in increasing PSP.The implementation of PG on PSP is applied to Regional Government Work Units (SKPD) in CentralJava with the moderating variables being environmental dynamics and human resource skills as controlvariables. Of the four PG elements have a positive effect on PSP, while the two variables of politicalstability and absence of violence and quality of regulations have no effect on PSP. All indicators ofenvironmental dynamics moderation have a positive effect on PSP, while control of HR skills can beused as their function.